Corporate real estate disposal impact on performance ratios - Louko, Antti (International Journal of Strategic Property Management, 2010)
The purpose of this study was to investigate the effects of corporate real estate disposals on corporate performance ratios in Europe between the years 1998–2002. In addition, it was studied whether the retail and telecom corporations that conducted large real estate disposals were in significantly worse condition before the transactions than other corporations in the same business sector. The study indicated that those retail corporations that had divested corporate real estate were less profitable compared to other corporations in the same business sector before the transactions. Similarly, some evidence was found that the telecom corporations that were disposing of real estate had worse capital structure and short‐term solvency before the transactions than other European telecom corporations. It seems, however, that the overall economical environment and other corporate operations have often influenced the development of the performance ratios more than the property disposals, at least in the most volatile business sectors.First Published Online: 18 Oct 2010